The investigation of impact induced particle resuspension - Kwa, Wilson Wei Sheng (2014)
Breathing in excessive airborne pollutants can be detrimental to one’s health which may lead to respiratory diseases. As humans spend up to 87% of their time indoors (Jenkins, Phillips, Mulberg, & Hui, 1992), it is of paramount importance to study the specific behaviour of particles in an indoor environment. Deposited particles would get resuspended under certain conditions while airborne particles would eventually settle. Past studies have already analysed the effects of aerodynamic forces from walking and adhesion forces. Hence, the key focus of this study is to investigate the assisted mechanical effects of various human activities on resuspension rates. The activities walking, construction, machinery and heavy traffic were simulated via a mechanical shaker in an experimental chamber which acted as the indoor environment. In addition, the effects of the following parameters, particle size (PM2.5, PM10 and 15-30µm) and flooring material were studied as well. A mathematical model was then proposed to describe the various particle behaviours in terms of their resuspension rates and deposition velocities. The results showed that higher vibration levels would give rise to higher resuspension and deposition rates. Only large enough vibration frequencies would generate enough removal force to overcome the adhesion forces between particle and surface. It was also concluded that carpet has the highest resuspension rates, followed by wood and vinyl. This was suggested to be caused by the fibres on carpet which reduced adhesion forces in particles. For particle sizes, it was observed that larger particles have higher resuspension and deposition rates and vice versa. Due to the potential effects of harmful aerosols, it is essential to enhance the understanding of particle behaviour. By extending the present model to include other effects like outdoor particle concentration and air filtration rate, it would allow people to apply necessary precautions against these contaminants. Understanding the respective resuspension and deposition mechanisms would also be useful to predict particle behaviours for any episodic event.